Concussive Symptoms Following Pediatric Mild Traumatic Brain Injury. Issue 4 (July 2020) - Yumul, Joy Noelle; McKinlay, Audrey; Than, Martin; Anderson, Vicki; Catroppa, Cathy
Abstract : Objectives: To determine the proportion of children with postconcussive symptoms (PCSs) and to explore the influence of noninjury and injury factors on parents' PCS report at 3 months postinjury. Design: A cross-sectional analysis of the 3-month postinjury data from a larger, prospective, longitudinal study. Methods: Parents and their child aged 2 to 12 years who presented at the emergency department with either a mild traumatic brain injury (mTBI) or a superficial injury to the head (SIH) were recruited. Parents reported their child's symptoms at the time of injury and at 3 months postinjury. Child, family/parent, and injury characteristics were considered as potential predictors. Logistic regression was conducted to determine which factors increase the likelihood of parents' PCS report. Results: At 3 months postinjury, 30% and 13% of children in the mTBI and SIH groups exhibited 1 or more symptoms, respectively. On the other hand, 18% (mTBI) and 8% (SIH) continued to have ongoing problems when 2 or more symptoms were considered at follow-up. The final model, which included child's sex, injury group, number of symptoms at the time of injury, and parental stress, had a significant predictive utility in determining parents' report of 1 or more symptoms at follow-up. Only parental stress continued to be a significant predictor when considering 2 or more symptoms at 3 months postinjury. Conclusions: Children with mTBI have worse outcomes than children with SIH at follow-up, with parents more likely to report 1 or more ongoing symptoms if their children had an mTBI. Postinjury assessment of parental stress and ongoing symptom monitoring in young children with mTBI will allow for timely provision of support for the family.